PENINGKATAN HASIL BELAJAR IPA DENGAN MODEL PROBLEM BASSED LEARNING DI KELAS IV SEKOLAH DASAR - Utami, Putri Dika; maimunah, maimunah; astimar, nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The research objective IPA describe the learning outcome with model Problem Bassed Learning in SDN 05 Bandar Buat grades IV. This research is a classroom action research using qualitative and quantitative approaches. His research interests of teachers and students of SDN 05 Bandar Buat grades IV. The results of the study the implementation of learning (aspects of teachers and students) the first cycle of the average value of percentage 75%(Good) and 77,5% (Very Good), the second cycle of the average value of percentage 87,5% (Very Good) and 92,5% (Very Good). The results of student learning first cycle the average value of percentage 72.54% (Good) and the second cycle the average value of percentage 87,9% % (Very Good).